Taking a partnership approach to embed physical activity in local policy and practice: a Bradford District case study - Jennifer Hall; Elliot Lever; Nathan Dawkins; Emma Young; Jamie Crowther; Rachel Williams; John Pickavance; Sally Barber; Andy Daly-Smith; Anna Chalkley; On behalf of the wider JU:MP team (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Supportive policy is an important component of a whole-systems approach to increasing physical activity and reducing inequalities. There is a growing body of literature surrounding the design and effectiveness of national policy approaches to physical activity, but evidence related to local-level approaches is lacking. The aim of this study was to examine ‘what works’, and identify factors underpinning change, focused on work to embed physical activity in local policy and practice in Bradford, UK. Methods A mixed-methods case study approach involved collecting data from cross-sectoral stakeholders directly or indirectly engaged in the physical activity agenda in Bradford over a period of three years (2021–2024). Data collection included focus groups, semi-structured interviews, researcher observations of key workshops and meetings, and surveys at two time-points (December 2021 and January 2024). Qualitative data were analysed using reflexive thematic analysis. Quantitative data were analysed using descriptive and inferential statistics. Results Four themes were identified which embody conditions that appear to be critical for working towards physical activity being embedded in local policy & practice within the Bradford District. These included: collaboration and sector integration, co-productive working, governance and leadership, and cultivating a learning culture. The process of co-producing a district-wide strategy for physical activity was key to facilitating shared ownership of the physical activity agenda across different levels of the system, and for supporting and maintaining cross-sectoral collaboration. On average, survey respondents connected with four more local organisations in relation to the physical activity agenda in January 2024 than in December 2021. Conclusion Taking a partnership approach, and fostering a culture of evidence-informed decision making, is key to embedding physical activity into policy and practice at a local level. Investing time to understand the aims and values of each partner, and potential synergies and tensions between them, can support the development of a positive and productive collaboration and, subsequently, more effective whole-system delivery and population-level increases in physical activity.